Chikungunya outbreak in Karachi Pakistan 2016-2017: an analysis of viral isolates - Dhani Prakoso; Kelli Barr; Kehkashan Imtiaz; Joveria Farooqi; Erum Khan; Maureen Long (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021